Pengaruh Pelatihan dan Motivasi Kerja terhadap Kinerja Karyawan di Bank BSI Kantor Cabang Suniaraja Bandung - Adi Indradi Wazdi; Ika Rarawahyuni; Ghea Tasya Firsttantia (Jurnal Dimamu, 2023)
Based on the results of observations, that the background of this research is the lack of training and low work motivation applied, causing not optimal employee performance at BSI KC Suniaraja Bandung. This study aims to determine how the influence of training and work motivation at Bank BSI Suniaraja Bandung partially or simultaneously. The object of research in this report is to measure the performance of employees at BSI KC Suniaraja Bandung. The type of research is quantitative associative with primary data types and uses data collection techniques in the form of observations, interviews, questionnaires, and literature studies. While the sample collection technique is non-probability sampling with saturated sample type. The population is all employees at BSI KC Suniaraja Bandung, amounting to 32 people with the same sample as the total population of 32 people. The results showed that there was a significant influence between training on employee performance with the results of the t test where the value of tcount > ttable (10.317 > 2.042), there was a significant influence between work motivation on employee performance with the test results t where t table (5,161 > 2,042), and simultaneously there is a significant influence between training and work motivation on employee performance at BSI KC Suniaraja Bandung with F test results where fcount > ftable (104.512 > 3,34).